Pro TypeScript Application-Scale JavaScript Development - Fenton, Steve (Apress, 2018)
Explore the features of this innovative open source language in depth, from working with the type system through object-orientation to understanding the runtime and the TypeScript compiler. This fully revised and updated second edition of Steve Fenton's popular book covers everything you need to discover this fascinating language and transform your experience of JavaScript development. What's New in This Edition: Coverage of major changes to modules, namespaces, and module loading New guidance on how to use inference to reduce the effort of using TypeScript Recommendations on compiler options A wide range of feature updates from intersections and tuples to async/await and the new approach to mixins What You'll Learn: Understand the TypeScript type system, and how to use it effectively Apply object-oriented design using TypeScript Use modules effectively to manage large programs Integrate existing frameworks and libraries into your TypeScript program.